Floating Solar Power Plants as a Sustainable Solution in Land-Constrained Areas: A Bibliometric Analysis - Rika Romatona; Andi Ramadhan; Dimas Juhar Panani; Sabikah Nur Naylah; Erza Arkan Zharif; Yuhani; Muhammad Ashbar As-Silmy (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
This study aims to analyze the development of research on floating photovoltaic (FPV) power plants as a sustainable solution for land-limited areas using a bibliometric approach. Data were collected from the Scopus database during 2015–2025 and analyzed using VOSviewer and Bibliometrix to examine publication trends, country productivity, keyword networks, and thematic development. The results show that FPV-related publications have increased significantly in recent years, with China emerging as the leading contributor to scientific output. Keyword analysis reveals that major research themes include solar energy, renewable energy, and solar power generation, while floating photovoltaic remains an evolving topic. In addition to addressing land scarcity issues, FPV technology offers additional benefits such as improved solar panel efficiency and reduced water evaporation. However, technical, economic, and environmental challenges remain important concerns for future studies. Overall, FPV demonstrates strong potential as an innovative renewable energy solution that supports sustainable energy development in areas with limited land availability.